Calculating when elective abdominal aortic aneurysm repair improves survival for individual patients : development of the Aneurysm Repair Decision Aid and economic evaluation /: development of the Aneurysm Repair Decision Aid and economic evaluation. (April 2015) - Grant, Stuart W (Stuart William)
No abstract available